A High‐Resolution Surface Mapping Procedure for Soil Cores Using Computed Tomography Scanning Data. Issue 6 (8th June 2017) - Han, Liwen; Whalen, Joann K.; Dutilleul, Pierre
Abstract : Core Ideas: Reliable surface representation is important for porosity analysis inside soil cores. High‐resolution soil surface maps are drawn from computed tomography scanning data. The moving‐window procedure presented here deals with artifacts and soil cavities. High‐resolution mapping of the soil surface provides insight regarding gas and water transport at the soil–atmosphere interface and biogeochemical reactions occurring in soil pores connected to the atmosphere. A new procedure for high‐resolution soil mapping was tested in undisturbed cores (15‐cm diameter) with images constructed from X‐ray computed tomography (CT) scanning. Our procedure includes detecting boundaries at the soil–air interface, edge cleaning, and removal of artifacts by use of a moving window with optimized size. We tested the procedure on three undisturbed soil cores from an agricultural field: (i) without introduced earthworms vs. in which earthworms of (ii) smaller ( Aporrectodea turgida Eisen) or (iii) larger ( Lumbricus terrestris L.) size were introduced and resided for 28 d. Soil surface maps were produced at a scale of 0.35‐ by 0.35‐mm pixels, with gray tones reflecting lower to higher elevation. This work has implications for describing pore connectivity and interpreting greenhouse gas fluxes from the soil.